The Implications of Coronavirus Outbreak on the Vocabularies and Language Styles of Arabic-speaking Indonesians - Febrianta, Rita; Daud, Daud Mohammed; Maiza, Zikrawahyuni (IAIN Salatiga, 2020)
This study examines the implications of the Corona pandemic in the vocabulary and style of non-native Arabic speakers in Indonesia. The aim of this study is to identify new vocabulary and phrases acquired by Indonesian teachers and students. The research method used is descriptive qualitative. The results showed that there were several vocabulary words, new phrases, and some specific terms used in teacher and student writing.